Handbook of tourism and quality-of-life research : enhancing the lives of tourists and residents of host communities - Uysal, Muzaffer; Perdue, Richard; Sirgy, M. Joseph (Dordrecht ; New York : Springer, 2012)
Quality of life (QOL) research in tourism has gained much momentum over the last two decades. Academics working in this area research issues related to tourists and host communities Practitioners are becoming increasingly interested in understanding the science that allows them to develop better marketing and managerial programs designed to enhance the quality of life of tourists. Tourism bureaus and government agencies are increasingly interested in issues of sustainable tourism, specifically in understanding and measuring the impact of tourism on the quality of life of the residents of the.
Prologue: tourism and quality-of-life (QOL) research: the missing links / Muzaffer Uysal, Richard R. Perdue, M. Joseph Sirgy -- pt. 1. tourism and QOL. Relationships and the tourism experience: challenges for quality-of-life assessments / Philip L. Pearce -- Positive psychology and tourism / Sebastian Filep -- The role of qualitative methods in tourism QOL research: a critique and future agenda / Vincent P. Magnini, John B. Ford, and Michael S. LaTour -- Poverty elimination through tourism dynamics / Manuel Vanegas, Sr. -- tourism, poverty relief, and the quality-of-life in developing countries / Robertico Croes -- tourism and quality-of-life: how does tourism measure up? / Janne J. Liburd, Pierre Benckendorff, and Jack Carlsen -- pt. 2. QOL from the perspectives of tourists. tourist consumption behavior and quality-of-life / Ruhet Genc -- Subjective aspects of tourists' quality-of-life (QOL) / Ruhet Genc -- Medical travel and the quality-of-life / Erik Cohen -- Physical, psychological, and social aspects of QOL medical tourism / Ruhet Genc -- Place affinities, lifestyle mobilities, and quality-of-life / Daniel R. Williams and Norman McIntyre -- tourist motivation and quality-of-life: in search of the missing link / Graham M.S. Dann -- Understanding the antecedents of destination identification: linkage between perceived quality-of-life, self-congruity, and destination identification / M. Mithat Uner and Can Armutlu -- An analysis of tourism QOL domains from the demand side / Laszlo Puczko and Melanie Smith -- Perceptions of tourism impacts and satisfaction with particular life domains / Philippus Stephanes (Stefan) Kruger -- Quality-of-life and travel motivations: integrating the two concepts in the Grevillea Model / Sara Dolnicar, Katie Lazarevski, and Venkata Yanamandram -- Relational tourism: observations on families and travel / Jay A. Mancini, Deepu V. George, and Bryce L. Jorgensen -- Impacts of the internet on travel satisfaction and overall life satisfaction / Soo Hyun Jun, Heather J. Hartwell, and Dimitrios Buhalis -- pt. 3. QOL from the perspectives of residents. Cultural tourism and the enhancement of quality-of-life / Bob McKercher and Pamela Ho -- Heritage, tourism and quality-of-life / Gregory J. ashworth and John E. Tunbridge -- Ethnic tourism and resident quality-of-life / Li Yang and Xiang (Robert) Li -- Alternative tourism as a contestable quality-of-life facilitator / David Weaver -- Building social capital to enhance the quality-of-life of destination residents / Gianna Moscardo -- The tourist area life cycle (TALC) and its effect on the quality-of-life (QOL) of destination community / Muzaffer Uysal, Eunju Woo, and Manisha Singal -- Relationship between carrying capacity of small island tourism destinations and quality-of-life / Deborah L. Kerstetter and Kelly S. Bricker -- Quality-of-life values among stakeholders in tourism destinations: a tale of converging and diverging interests and conflicts / Klaus Weiermair and Mike Peters -- Stakeholder engagement in tourism planning and development / Lisa C. Chase, Benoni Amsden, and Rhonda G. Phillips -- Destination competitiveness and its implications for host-community QOL / Geoffrey I. Crouch and J.R. Brent Ritchie -- Destination management, competitiveness, and quality-of-life: a review of literature and research agenda / B. Bynhum Boley and Richard R. Perdue -- Destination management and quality-of-life / Ige Prnar and Ebru Gunlu -- Community participation in tourism planning and development / Amir Shani and Abraham Pizam -- The role of tourism in sustainable communities / Timothy J. Tyrrell and Robert J. Johnston -- Exploring the causal nexus of tourism impacts on quality-of-life / Jeffrey Michael Rempel -- Rural tourism and second home development: the case of Colorado / Patrick Long ... [et al.] -- The effect of tourism on the housing market / Bianca Biagi, Dionysia Lambiri, and Alessandra Faggian -- Resident quality-of-life in gaming communities / Patricia A. Stokowski and Minkyung Park -- pt. 4. Epilogue. The missing links and future research directions / Muzaffer Uysal, Richard R. Perdue, M. Joseph Sirgy.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Tourism -- Social aspects; Quality of life; Sustainable tourism; Culture and tourism; Tourists -- Services for